Cerebellar lesions in a patient with anti‐myelin oligodendrocyte glycoprotein antibody‐associated encephalitis. Issue 4 (5th September 2019) - Fujimori, Juichi; Nakashima, Ichiro
Abstract : Cerebellar lesions adjacent to the fourth ventricle that involved the bilateral dentate nucleus were observed in a patient with anti‐myelin oligodendrocyte glycoprotein antibody‐associated encephalitis.